Reinke’s Edema: investigations on the role of MIB-1 and hepatocyte growth factor - M. Artico; E. Bronzetti; B. Ionta; M. Bruno; A. Greco; G. Ruoppolo; A. De Virgilio; L. Longo; M. De Vincentiis (European Journal of Histochemistry, 2010)
Reinke’s edema is a benign disease of the human vocal fold, which mainly affects the sub-epithelial layer of the vocal fold. Microscopic observations show a strongly oedematous epithelium with loosened intercellular junctions, a disruption of the extracellular connections between mucosal epithelium and connective tissue, closely adherent to the thyroarytenoid muscle. Thickening of the basal layer of epithelium, known as Reinke’s space, high deposition of fibronectin and chronic inflammatory infiltration it is also visible. We analyzed, together with the hepatocyte growth factor (HGF), the expression level of MIB-1 in samples harvested from patients affected by Reinke’s edema, in order to define its biological role and consider it as a possible prognostic factor in the follow-up after surgical treatment. We observed a moderate expression of HGF in the lamina propria of the human vocal fold and in the basal membrane of the mucosal epithelium. Our finding suggests that this growth factor acts as an anti – fibrotic agent in Reinke’s space and affects the fibronectin deposition in the lamina propria. MIB-1, on the contrary, showed a weak expression in the basement membrane of the mucosal epithelium and a total absence in the lamina propria deep layer, thus suggesting that only the superficial layer is actively involved in the reparatory process with a high regenerative capacity, together with a high deposition of fibronectin. The latter is necessary for the cellular connections reconstruction, after the inflammatory infiltration.